1989
DOI: 10.1126/science.2475909
|View full text |Cite
|
Sign up to set email alerts
|

Subplate Neurons Pioneer the First Axon Pathway from the Cerebral Cortex

Abstract: During the development of the nervous system, growing axons must traverse considerable distances to find their targets. In insects, this problem is solved in part by pioneer neurons, which lay down the first axonal pathways when distances are at a minimum. Here the existence of a similar kind of neuron in the developing mammalian telencephalon is described. These are the subplate cells, the first postmitotic neurons of the cerebral cortex. Axons from subplate neurons traverse the internal capsule and invade th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
405
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 621 publications
(421 citation statements)
references
References 27 publications
16
405
0
Order By: Relevance
“…Several studies have examined the early development of these projections and have identified pioneering axonal populations as well as potential intermediate targets and choice points for these axons (McConnell et al, 1989;De Carlos and O'Leary, 1992;Métin and Godement, 1996;Molnár et al, 1998;Braisted et al, 1999;Tuttle et al, 1999;Auladell et al, 2000;Ló pez-Bendito et al, 2006). In addition, multiple molecules that participate in the guidance of these connections have been identified, providing a comprehensive frame in which to understand their development (Serafini et al, 1996;Métin et al, 1997;Richards et al, 1997;Braisted et al, 2000;Leighton et al, 2001;Bagri et al, 2002;Ló pez-Bendito et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the early development of these projections and have identified pioneering axonal populations as well as potential intermediate targets and choice points for these axons (McConnell et al, 1989;De Carlos and O'Leary, 1992;Métin and Godement, 1996;Molnár et al, 1998;Braisted et al, 1999;Tuttle et al, 1999;Auladell et al, 2000;Ló pez-Bendito et al, 2006). In addition, multiple molecules that participate in the guidance of these connections have been identified, providing a comprehensive frame in which to understand their development (Serafini et al, 1996;Métin et al, 1997;Richards et al, 1997;Braisted et al, 2000;Leighton et al, 2001;Bagri et al, 2002;Ló pez-Bendito et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…There were two GABA-IR cell layers (the preplate and the lower I Z) in the early embryos (E14 -E15) and three layers (the marginal zone, the subplate, and the lower IZ) later, after the insertion of the cortical plate. The marginal zone contains different types of cells that have functions different from those of the subplate neurons (Shatz et al, 1988;McConnell et al, 1989McConnell et al, , 1990D'Arcangelo et al, 1995;Ogawa et al, 1995). Similarly, the subplate and the IZ were assumed to have different types of cells and different functions.…”
Section: Tangentially Migrating Map2-positive Cells Are a Distinct Pomentioning
confidence: 99%
“…Layer 5 cells are born between E12 and E15.5 (Polleux et al, 1997) and migrate to the cortical plate until at least E18. It is believed that the first cell population to extend corticothalamic axons are the subplate neurons, followed shortly afterward by axons from the developing cortical plate (McConnell et al, 1989;De Carlos and O'Leary, 1992;Auladell et al, 2000). At E12, cortical axonal processes extend laterally and course in the intermediate zone parallel to the pial surface.…”
Section: Time Schedule For Development Of Thalamocortical and Corticomentioning
confidence: 99%